Diverted total syntheses of potent cell adhesion inhibitor peribysin E analogues - Handore, Kishor L.; Reddy, D. Srinivasa (Organic Letters, 2013)
Preliminary results from a program aimed at the creation of a focused library of analogues around the natural product peribysin E, a potent biologically active and structurally fascinating molecule, are reported. The total synthesis of (+/-)-peribysin E was accomplished using a short route. Eight new analogues of the natural compound have been accomplished by means of ``diverted total synthesis'' in less than 10 steps. The present effort highlights protecting-group-free total syntheses and the shortest route to access these functionally embellished hydrindanes.